Estetika Struktur Atap Tajug pada Masjid Tradisional Jawa sebagai Manifestasi Konsep Spiritual Islam - Ahid Rizqy Sutanto; Wafa Aulia Hasbullah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
Traditional mosques on the island of Java possess distinctive architectural characteristics through the use of the tajug (tiered) roof, which differentiates them from mosque typologies commonly found in the Middle East. Beyond serving as a structural element and a response to tropical climatic conditions, the tajug roof also embodies profound philosophical and spiritual values. This study aims to examine the spiritual aesthetic meanings embedded in the tajug roof structure of traditional Javanese mosques through the Basis of Thinking approach. The research employs a qualitative method with a library research approach. Data were collected from various secondary sources, including scientific journals, books on Nusantara architecture, and literature concerning Javanese cosmology and Islamic mysticism. The analysis was conducted by identifying the structural components of the tajug roof and relating them to the concepts of Islamic spirituality. The findings reveal that the vertical and tiered arrangement of the tajug roof functions not only as a technical solution to the tropical climate but also as a representation of the spiritual journey toward Ma’rifatullah through the stages of Sharia, Tariqa, Haqiqa, and Ma’rifa. Architectural elements such as the soko guru, tiers, brunjung, and mustaka contain Islamic symbolism that reinforces the value of tawhid within the worship space. Furthermore, the form and construction of the tajug roof demonstrate a harmonious integration of ecological functions, local wisdom, and Islamic teachings. Therefore, traditional Javanese mosque architecture can be understood as a medium of spiritual expression that integrates vernacular intelligence with Islamic theological values.